Cavitation Analysis of a Propeller Based on Variations in Water Temperature and Propeller Rotational Speed Using CFD Simulation - Dian Febriyanti (Applied Science and Technology on Naval Engineering, 2026)
This study aims to understand how the cavitation phenomenon occurs in ship propellers by varying the water flow temperature and propeller rotation speed. Cavitation is a condition in which fluid pressure decreases to below vapor pressure, so that vapor bubbles are formed that can damage the propeller surface. Therefore, it is important to conduct an analysis to find out where cavitation first appears and how it affects the thrust generated by the propeller. This study uses Computational Fluid Dynamics (CFD) software. Variations in temperature and rotational speed are applied to see the differences in the results of the propeller thrust coefficient values ​​in each condition. The simulation results show that changes in fluid temperature do not have a significant effect on the occurrence of cavitation. However, increasing the propeller rotational speed clearly increases the potential for cavitation. At a speed of 800 RPM cavitation has not been seen, either at temperatures of 17oC, 21oC, and 30oC. However, at a speed of 1600 RPM cavitation appears, both at temperatures of 17oC, 21oC, and 30oC. This shows that temperature does not have a significant effect, but rotational speed is a very influential factor in the process of cavitation and propulsion efficiency.